Method for producing recycled cathode material precursor and recycled cathode material, as well as method for using recycled cathode material

The method addresses the challenges of recycling lithium-ion battery materials by using heat treatment and subsequent chemical processing to produce high-quality recycled positive electrode materials with low environmental and economic burdens.

JP2025066488APending Publication Date: 2025-04-23DOWA HOLDINGS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023176142
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

Existing methods for recycling metal materials from spent lithium-ion secondary batteries are costly and environmentally burdensome, requiring complex separation steps and high-cost extractants, and pose safety risks due to the need for dismantling robust battery packages.

Method used

A method involving heat treatment of spent lithium-ion battery cells to safely and efficiently remove positive electrode active material, followed by mechanical and magnetic recovery, acid leaching, iron removal, ion exchange, and alkali treatment to produce a recycled positive electrode material precursor with low aluminum, copper, and iron content.

Benefits of technology

This method enables the production of recycled positive electrode materials with high safety, low environmental impact, and reduced recycling costs, maintaining battery performance and allowing for efficient processing of large quantities of spent batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066488000001_ABST
    Figure 2025066488000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a recycled cathode material precursor and a recycled cathode material with low content of aluminum, copper, and iron, high safety, low environmental load, and low recycling cost, from lithium-ion secondary batteries that are objects to be processed.SOLUTION: A production method for producing a recycled cathode material precursor from lithium-ion secondary batteries, which are objects to be processed, includes performing a heating step, a crushing step, a classification and sorting step, a magnetic separation step, an acid leaching step, an iron removal step, an ion exchange step, an alkaline treatment step, and a washing step on the lithium-ion secondary batteries that are objects to be processed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled cathode material precursor and a recycled cathode material from materials recovered from lithium ion secondary batteries, which are the subject of treatment, and a method for using the recycled cathode material. [Background technology]

[0002] Lithium-ion secondary batteries are rapidly expanding their applications from the electronics field to the automotive field. In particular, in the automotive field, it is expected that the demand for large batteries will rapidly increase due to the increase in unit capacity for hybrid and electric vehicle applications, such as plug-in hybrid vehicles (PHEVs) and battery electric vehicles (BEVs). The rapid increase in demand for large batteries is also due to the strong demand for reducing CO2 emissions in the transportation industry. As the demand for lithium-ion secondary batteries increases, the amount of lithium-ion secondary batteries that have reached the end of their product life will also increase. Hereafter, lithium-ion secondary batteries will also be referred to as "LIBs."

[0003] On the other hand, since LIBs use expensive metallic materials as their positive electrode material, recycling the metallic materials from LIBs that have reached the end of their product life is an important industrial issue.

[0004] For example, in Patent Document 1, impurities are removed from waste batteries, waste positive electrode materials, or mixtures thereof that contain impurities and a metal group consisting of at least two metals selected from Co, Ni, and Mn, and the metal group is recovered as a mixture of metal salts. Patent Document 1 also proposes producing a positive electrode material using the recovered mixture of metal salts.

[0005] For example, Patent Document 2 filed by the present applicants discloses a recycled positive electrode material containing a predetermined amount of at least one of iron, copper, and aluminum. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5847742 [Patent Document 2] Patent No. 7176707 Summary of the Invention [Problem to be solved by the invention]

[0007] In order to recycle metal materials from waste LIBs that have reached the end of their product life, it is necessary to reduce the environmental impact and the cost of recycling. However, for example, the method described in Patent Document 1 uses complicated separation steps and a large number of expensive extractants, and there are concerns that the environmental impact and cost of recycling are large.

[0008] For example, LIB cells for vehicles such as PHEVs and BEVs require robust packaging that can withstand strong mechanical impacts, ingress of all kinds of liquids, fire, and high temperatures. The LIB stack in a LIB cell is usually disassembled into internal parts (positive electrode, negative electrode, separator) and an exterior cover. The method described in Patent Document 1 requires dismantling the cell. Therefore, the method described in Patent Document 1 requires safety measures. In addition, the robust packaging of the LIB stack complicates mechanically removing the positive electrode active material from the cell. This will become a more prominent issue if the demand for large batteries mentioned above increases sharply and the amount of waste LIBs to be processed increases.

[0009] In contrast to the method described in Patent Document 1, which requires dismantling LIB cells, which requires safety measures, the method described in Patent Document 2 involves heat treatment of each waste LIB cell as a measure to automatically and safely extract the positive electrode active material from the waste LIB cells in a time-efficient manner. This heat treatment renders the LIB stack inside the cell electrically and chemically harmless, significantly reducing the risk.

[0010] By adopting this method, the positive electrode active material can be extracted from the LIB stack in a time-efficient, safe manner, and in an electrically and chemically harmless manner, without the need for complex mechanical disassembly.

[0011] In addition, the recycled positive electrode material described in Patent Document 2 contains a predetermined amount of at least one of aluminum, copper, and iron, which suggests that the energy density and output density are maintained high even after charge / discharge cycles, and thus has sufficient added value in terms of battery performance in recycled LIBs. However, as a result of the inventors' investigations, it was found that, depending on the contents of the waste LIBs to be recycled and used, the characteristics of batteries using the recycled positive electrode material can be improved by using a recycled positive electrode material with a low content of aluminum, copper, and iron.

[0012] The present invention was made under the above-mentioned circumstances, and the problem to be solved by the present invention relates to a method for producing a recycled positive electrode material precursor from the treated object, that is, a LIB, which has a low environmental impact, low recycling costs, high safety, and low contents of aluminum, copper, and iron, a method for producing recycled positive electrode material from the recycled positive electrode material precursor, and a method for using the recycled positive electrode material, which involves assembling a LIB using the recycled positive electrode material and carrying out an activation process for charging and discharging. [Means for solving the problem]

[0013] The first invention to solve the above problem is: A method for producing a recycled positive electrode material precursor from a lithium ion secondary battery, which is an object to be treated, comprising the steps of: a heat treatment step of heating the lithium ion secondary battery as the object to be treated to obtain a heat-treated product; A crushing step of crushing the heat-treated product to obtain a crushed product; A classification and selection step of performing classification and selection on the crushed product to obtain a fine product; an acid leaching step of subjecting the fine product to acid leaching to obtain an acid leachate; an iron removing step of adding an oxidizing agent and an alkali to the acid leaching solution to obtain an iron-removed solution; an ion exchange step of contacting the iron-removed liquid with a chelating resin to obtain an ion-exchanged liquid; an alkali treatment step of adding an alkali to the post-ion exchange liquid to generate a precipitate; and a washing step of washing the precipitate with water to obtain a regenerated cathode material precursor. The second invention is In the method for producing a regenerated positive electrode material precursor according to the first aspect of the present invention, a magnetic separation step is carried out after the classification step, in which the fine product is subjected to magnetic separation to obtain a magnetic material. The third invention is In the method for producing a recycled positive electrode material precursor according to the first aspect of the present invention, the acid leaching step is carried out using sulfuric acid. The fourth invention is This is the method for producing a regenerated cathode material precursor according to the first aspect of the present invention, wherein the iron removal step is performed by using an aqueous hydrogen peroxide solution as an oxidizing agent and setting the oxidation-reduction potential of the acid leaching solution to 500 to 750 mV (Ag / AgCl). The fifth invention is In the ion exchange step, an aminomethyl phosphate-based chelating resin is used as the chelating resin to remove aluminum ions, which is the method for producing a regenerated positive electrode material precursor according to the first aspect of the present invention. The sixth invention is The method for producing a recycled cathode material precursor according to the first aspect of the present invention includes carrying out an analysis step of quantitatively analyzing metal elements contained in the post-ion exchange liquid, and carrying out a preparation step of preparing the post-ion exchange liquid when there is a difference between the result of the quantitative analysis of metal elements contained in the post-ion exchange liquid and the target metal composition of the recycled cathode material precursor. The seventh invention is The method for producing a recycled positive electrode material precursor according to the first aspect of the present invention includes carrying out an analysis step of quantitatively analyzing the metal elements contained in the post-ion exchange liquid, and, if there is a difference between the result of the quantitative analysis of the metal elements contained in the post-ion exchange liquid and the target metal composition of the recycled positive electrode material precursor, carrying out an addition step of adding metal elements that are deficient in the target metal composition of the recycled positive electrode material precursor. The eighth invention is A sixth aspect of the present invention relates to a method for producing a regenerated positive electrode material precursor, wherein the prepared post-ion exchange solution has an aluminum content of 100 mg / L or less, a copper content of 1 mg / L or less, and an iron content of 1 mg / L or less. The ninth invention is A seventh aspect of the present invention provides a method for producing a recycled positive electrode material precursor, wherein the post-ion exchange liquid to which the metal elements have been added has an aluminum content of 100 mg / L or less, a copper content of 1 mg / L or less, and an iron content of 1 mg / L or less. The tenth invention is This is a method for producing a recycled cathode material, which comprises adding a predetermined metal compound to a recycled cathode material precursor produced by the method for producing a recycled cathode material precursor according to any one of the first to ninth aspects of the present invention, and then calcining the mixture to obtain a recycled cathode material. The eleventh invention is A tenth aspect of the present invention relates to a method for producing a recycled positive electrode material, wherein the metal compound is at least one selected from the group consisting of a lithium compound, a nickel compound, a cobalt compound, and a manganese compound. The twelfth invention is An assembly process for assembling a lithium ion secondary battery having the recycled positive electrode material according to the tenth aspect of the present invention; and an activation step of charging and discharging the lithium ion secondary battery assembled in the assembly step. Effect of the Invention

[0014] According to the present invention, it is possible to produce recycled positive electrode material precursors and recycled positive electrode materials from the LIBs to be treated, with little environmental impact, low recycling costs, and high safety. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a manufacturing flow diagram of a recycled cathode material precursor and a recycled cathode material according to the present invention. [Diagram 2] FIG. 1 is a schematic diagram of an example of a coin cell type lithium ion secondary battery used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a method for producing a recycled cathode material precursor and a recycled cathode material, which are embodiments for carrying out the present invention, will be described with reference to FIG. 1, which is a manufacturing flow diagram. "~" indicates a predetermined value or more and a predetermined value or less. This embodiment will be described in the following order. [1. Findings regarding the manufacturing method of the present invention] [2. Lithium-ion secondary battery as the object to be treated] [3. Method for producing recycled cathode material precursor] (3-1. Heat treatment process) (3-2. Crushing process) (3-3. Classification and sorting process) (3-4.Magnetic selection process) (3-5. Acid leaching process) (3-6. Iron removal process) (3-7. Ion exchange process) (3-8. Alkaline treatment process) (3-9. Cleaning process) [4. Manufacturing method of recycled cathode material] (4-1. Addition process of lithium source, etc.) (4-2. Grinding and mixing process) (4-3. Firing process) (4-4. Crushing process) [5. How to use recycled cathode materials] (5-1. Regenerated positive electrode) (5-2. Lithium-ion secondary battery using recycled positive electrode material according to the present invention) [6. Effects of the present invention]

[0017] [1. Findings regarding the manufacturing method of the present invention] In order to solve the problems of the present invention, the present inventors have conducted extensive research and have come up with the following method.

[0018] As a measure to automatically and safely extract the positive electrode active material from the cells of used LIBs in a time-efficient manner, heat treatment is carried out on each used LIB cell. This heat treatment renders the LIB stack inside the cell electrically and chemically harmless, significantly reducing the risk.

[0019] Mechanical and magnetic recovery of the cathode active material from the heat-treated LIB stacks allows for the enrichment of e.g. Ni, Co, and Mn in the pyrolysis residue. The pyrolysis residue enriched in Ni, Co, and Mn can be converted into a mixture of Ni, Co, and Mn hydroxides (e.g., a precursor of the cathode active material).

[0020] By adopting this method, the positive electrode active material can be extracted from the LIB laminate in a time-efficient and safe manner that is electrically and chemically harmless without complex mechanical disassembly. These advantages can bring the benefit of automating the processing of waste LIBs. Hereafter, the LIB laminate may be simply referred to as LIB.

[0021] [2. Lithium-ion secondary battery as the object to be treated] The LIBs to be treated are not particularly limited and can be appropriately selected depending on the purpose. Examples include defective LIBs generated during the LIB manufacturing process, LIBs that are discarded due to defects in the equipment used or the end of the life of the equipment, and used LIBs that are discarded due to the end of their life.

[0022] LIBs are secondary batteries that charge and discharge by the movement of lithium ions between a positive electrode and a negative electrode. For example, LIBs include a positive electrode, a negative electrode, a separator, an electrolyte (an electrolytic solution containing an organic solvent or a solid electrolyte), and an outer container that is a battery case.

[0023] There are no particular limitations on the shape, structure, size, material, etc. of the LIB to be treated, and these can be appropriately selected depending on the purpose. Examples of the shape of the LIB include laminate type, cylindrical type, button type, coin type, rectangular type, flat type, etc.

[0024] The positive electrode is not particularly limited as long as it has a positive electrode material on a positive electrode current collector, and can be appropriately selected depending on the purpose. The shape of the positive electrode is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a flat plate shape and a sheet shape.

[0025] The shape, structure, size, material, etc. of the positive electrode current collector are not particularly limited, and can be appropriately selected according to the purpose. The shape of the positive electrode current collector can be, for example, a foil shape. The material of the positive electrode current collector can be, for example, stainless steel, nickel, aluminum, copper, titanium, tantalum, etc. Among these, aluminum is often used.

[0026] The constituent members of the positive electrode material can be appropriately selected depending on the purpose, and examples thereof include a positive electrode material that contains at least a positive electrode active material containing a rare valuable material, and optionally contains a conductive agent and a binder resin. There are no particular limitations on the rare valuable material, and it can be appropriately selected depending on the purpose, but cobalt, nickel, and manganese (sometimes referred to as "NCM" in the present invention; cobalt, nickel, and aluminum are sometimes referred to as "NCA") are frequently used.

[0027] The positive electrode active material may be a lithium transition metal oxide (LTMO). Examples of LTMO include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), and lithium cobalt nickel oxide (LiCo 1 / 2 Ni 1 / 2 O2), ternary materials (LiNi based on NCM x Co y Mn z O2) (x+y+z=1, and x, y, and z are each greater than 0 and less than 1) (hereinafter, also referred to as NCM, even if it contains Li), or a compound of any combination of each of them.

[0028] Among them, the above-mentioned NCM LiNi containing equal amounts of Ni, Co, and Mn (x=y=z=1 / 3) 1 / 3Co 1 / 3 Mn 1 / 3 O2 exhibits good Li-ion extraction / insertion properties when used as a positive electrode material in LIBs, making it suitable for automotive applications.

[0029] On the other hand, Ni in ternary LTMOs is useful for providing high specific capacity with slow Li-ion extraction / insertion in cells with low charge / discharge current densities. LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2 is also considered promising as a positive electrode active material for LIBs for automobiles, such as BEVs and PHEVs.

[0030] The conductive agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the conductive agent include carbon black, graphite, carbon fiber, and metal carbides.

[0031] The binder resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the binder resin include homopolymers or copolymers of vinylidene fluoride, tetrafluoroethylene, acrylonitrile, ethylene oxide, and the like, and styrene-butadiene rubber.

[0032] The negative electrode is not particularly limited as long as it has a negative electrode material on a negative electrode current collector, and can be appropriately selected depending on the purpose. The shape of the negative electrode is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a flat plate shape and a sheet shape.

[0033] The shape, structure, size, material, etc. of the negative electrode current collector are not particularly limited, and can be appropriately selected according to the purpose. Examples of the shape of the negative electrode current collector include foil. Examples of the material of the negative electrode current collector include stainless steel, nickel, aluminum, copper, titanium, and tantalum. Among these, copper is often used.

[0034] The negative electrode material is not particularly limited and can be appropriately selected depending on the purpose. Examples of the negative electrode material include carbon materials such as graphite and hard carbon, titanate, silicon, and composites of these materials.

[0035] The positive electrode current collector and the negative electrode current collector have a laminate structure, and the laminate is not particularly limited and can be appropriately selected depending on the purpose.

[0036] [3. Method for producing recycled cathode material precursor] (3-1. Heat treatment process) As shown in FIG. 1, first, a heat treatment process is performed on the LIB to be treated. The heat treatment temperature is not particularly limited as long as it is equal to or higher than the melting point of the current collector with the lower melting point and lower than the melting point of the current collector with the higher melting point among the positive electrode current collector and the negative electrode current collector, and can be appropriately selected according to the purpose. However, it is preferably 670°C or higher, more preferably 670°C to 1100°C, even more preferably 700°C or higher, and particularly preferably 700°C to 900°C. If the heat treatment temperature is 670°C or higher, embrittlement of the current collector with the lower melting point occurs sufficiently, and if it is 1100°C or lower, embrittlement of both the current collector with the lower melting point and the current collector with the higher melting point and the outer container can be suppressed, and the separation efficiency of the current collector and the outer container by crushing and classification can be maintained. In addition, if the outer container of the LIB melts during the heat treatment, the metal derived from the outer container and the electrode part can be easily separated by placing a tray for collecting the molten metal under the LIB.

[0037] By performing heat treatment at a predetermined heat treatment temperature, for example, in a laminate in which the positive electrode collector is aluminum and the negative electrode collector is copper, the positive electrode collector made of aluminum foil becomes embrittled and is easily granulated in the crushing process described below. The embrittlement of the positive electrode collector occurs due to melting or oxidation reaction. In addition, the aluminum that melts and flows down is collected in a tray. On the other hand, the negative electrode collector made of copper is heat treated at a temperature below the melting point of copper, so it does not melt and can be highly selected in the dry magnetic sorting process described below. In addition, when either the laminate or the LIB is placed in an oxygen-shielding container and heat treated, the positive electrode collector made of aluminum foil melts and becomes embrittled, making it easy to granulate in the crushing process described below, while the negative electrode collector made of copper is heat treated under a low oxygen partial pressure due to the oxygen shielding effect of the oxygen-shielding container and the reduction effect of the negative electrode active material such as carbon contained in the laminate or LIB, so embrittlement due to oxidation does not occur. Therefore, the positive electrode current collector is finely crushed by crushing in the crushing step, while the negative electrode current collector remains as coarse particles even after crushing, which enables more effective and high-level sorting in the classification and sorting step described below.

[0038] The heat treatment time is not particularly limited and can be appropriately selected depending on the purpose, but may be 1 minute or more, 5 hours or less, 2 hours or less, or 1 hour or less. The heat treatment time may be a heat treatment time that allows the current collector with a low melting point to reach a desired temperature, and the holding time may be short. If the heat treatment time is within a particularly preferred range, it is advantageous in terms of the cost required for the heat treatment.

[0039] The heat treatment method is not particularly limited and can be appropriately selected depending on the purpose, for example, heat treatment can be performed using a heat treatment furnace, such as a rotary kiln, a fluidized bed furnace, a tunnel furnace, a batch furnace such as a muffle, a cupola, a stoker furnace, etc.

[0040] The atmosphere used for the heat treatment is not particularly limited and can be appropriately selected depending on the purpose, and can be carried out in air. However, an atmosphere with a low oxygen concentration is preferable because it allows the metals derived from the positive electrode current collector and the metals derived from the negative electrode current collector to be recovered in high quality and at a high recovery rate.

[0041] As a method for realizing the low-oxygen atmosphere, the LIB or the laminate may be placed in an oxygen-shielding container and heat-treated. The material of the oxygen-shielding container is not particularly limited as long as it is a material that does not melt at the heat treatment temperature described above, and can be appropriately selected depending on the purpose, and examples thereof include iron and stainless steel. In order to release the gas pressure caused by the combustion of the electrolyte in the LIB or the laminate, it is preferable to provide an opening in the oxygen-shielding container. It is preferable that the opening area of ​​the opening is 12.5% ​​or less of the surface area of ​​the outer container in which the opening is provided. It is more preferable that the opening area of ​​the opening is 6.3% or less of the surface area of ​​the outer container in which the opening is provided. If the opening area of ​​the opening exceeds 12.5% ​​of the surface area of ​​the outer container, most of the current collector is easily oxidized by the heat treatment. There is no particular limitation on the shape, size, and formation location of the opening, and it can be appropriately selected depending on the purpose.

[0042] Ultimately, it is sufficient to heat-treat the LIB or laminate at high temperature (e.g., 800°C) in an oxygen-free or low-oxygen state. Therefore, even without using the oxygen-shielding container, the LIB may be heat-treated in a heat treatment furnace after blocking the air supply or reducing the amount of air supplied (e.g., 11% or less in terms of oxygen concentration).

[0043] Here, if desired, it is also preferable to perform a qualitative and quantitative analysis of the metal elements contained in the heat-treated product obtained in the heat treatment step using X-ray fluorescence analysis or the like, because the metal components contained in the heat-treated product may differ depending on the LIB being treated.

[0044] Based on the results of this qualitative and quantitative analysis, it is preferable to group heat-treated products having similar metal component compositions and send the heat-treated products separated into groups to the crushing process described below in order to stabilize the composition of the metal components of the recycled positive electrode material.

[0045] (3-2. Crushing process) Next, a crushing step is carried out to crush the heat-treated product obtained in the heat treatment step. In the crushing step, the heat-treated product is preferably crushed by impact to obtain crushed products.

[0046] The crushing method is not particularly limited and can be appropriately selected depending on the purpose. Examples of the crushing method by impact include a method of throwing the heat-treated material with a rotating striking plate and hitting it against a collision plate to give an impact, and a method of hitting the heat-treated material with a rotating striker (beater), which can be performed using, for example, a hammer crusher or a chain crusher. Examples of the method of hitting the heat-treated material with balls or rods made of ceramic or iron, which can be performed using a ball mill or a rod mill. Crushing can also be performed by using a biaxial crusher with a short blade width and blade length for crushing by compression.

[0047] Obtaining crushed material by impact promotes crushing of the active material and the low melting point current collector, while the high melting point current collector, whose shape has not changed significantly, exists in a form such as foil, etc. Therefore, in the crushing process, the high melting point current collector is merely cut, and the high melting point current collector is less likely to be granulated compared to the low melting point current collector, so that a crushed material can be obtained in a state in which the low melting point current collector and the high melting point current collector can be efficiently separated in the classification and selection process described later.

[0048] The crushing time is not particularly limited and can be appropriately selected depending on the purpose, but the processing time per kg of LIB is preferably 1 second to 30 minutes, more preferably 2 seconds to 10 minutes, and particularly preferably 3 seconds to 5 minutes. If the crushing time is less than 1 second, the LIB may not be crushed, and if it exceeds 30 minutes, the LIB may be crushed excessively. It is preferable that the maximum particle size of the crushed material is 10 mm or less.

[0049] (3-3. Classification and sorting process) Next, as a physical sorting step, a classification sorting step can be carried out in which the crushed product obtained in the crushing step is classified into a coarse product and a fine product. The classification method is not particularly limited and can be appropriately selected depending on the purpose. For example, the classification can be carried out using a vibrating sieve, a multi-stage vibrating sieve, a cyclone, a JIS Z8801 standard sieve, a wet vibrating table, an air table, etc.

[0050] The classification point used in the classification and sorting process can be appropriately selected according to the purpose as long as it is 0.45 mm or more. For example, it is desirable to use a classification point of 0.6 to 2.4 mm. If the classification point exceeds 2.4 mm, the inclusion of metals originating from the outer packaging and metals with higher melting points in the fine product increases, and the separation performance from cobalt, nickel, and manganese originating from the active material may decrease. On the other hand, if the classification point is less than 0.6 mm, the inclusion of metals originating from the low melting point current collector and active material in the coarse product increases, the quality of metals originating from the high melting point current collector in the coarse product decreases, and the recovery rate of cobalt, nickel, and manganese originating from the active material in the fine product may be less than 60%.

[0051] In addition, when a sieve is used as a classification method, by placing a crushing promoter, such as stainless steel balls or alumina balls, on the sieve and then sieving, small crushed pieces attached to large crushed pieces can be separated from the large crushed pieces, and the large crushed pieces and small crushed pieces can be separated more efficiently. This can further improve the quality of the recovered metal. The crushing process and the classification and sorting process can also be carried out simultaneously. For example, the heat-treated product obtained in the heat treatment process can be crushed while the crushed pieces are classified into coarse and fine products (crushing and classification).

[0052] By the above classification, metals derived from the outer container and the current collector with a high melting point can be recovered as a coarse product, and cobalt, nickel, manganese, and lithium derived from the active material can be recovered as a fine product (black mass (also called black powder)). The fine product may be classified again. By removing fine particles of, for example, 150 μm or less from the fine material by this second classification, the amount of negative electrode active material contained in the non-magnetic material from the wet magnetic separation (hereinafter, magnetic separation will be abbreviated to magnetic separation) can be reduced.

[0053] (3-4.Magnetic selection process) As a physical separation process, the crushed material obtained in the crushing process or the coarse product obtained in the classification and separation process can be subjected to a dry magnetic separation process. Iron is recovered as a magnetic material, and metals derived from the negative electrode current collector, such as copper, are recovered as non-magnetic materials.

[0054] As a physical separation step, the crushed material obtained in the crushing step or the fine product (black mass) obtained in the classification step can be preferably subjected to a wet magnetic separation step (wet magnetic separation). Cobalt and nickel are recovered as magnetic materials. When the fine product (black mass) obtained in the classification step is magnetically separated by dry magnetic separation, the particles aggregate due to the moisture adhering between the particles, and the negative electrode current collector-derived metal particles and the negative electrode active material fine particles contained in the fine product at 10% or more and the cobalt-nickel particles cannot be sufficiently separated. In the present invention, the material derived from the negative electrode active material and the metal derived from the negative electrode current collector are separated into a non-magnetic product slurry in the wet magnetic separation step, and a magnetic material (black mass magnetic material) containing cobalt and nickel can be recovered. Note that manganese is not ferromagnetic at room temperature, but when it forms a composite oxide with cobalt and nickel in a LIB, it accompanies the cobalt and nickel when they are magnetically separated. Therefore, a considerable amount of manganese is also recovered by magnetic separation. The magnetic force during magnetic separation is preferably 1500 to 8000G.

[0055] (3-5. Acid leaching process) In this process, acids such as H2SO4, HCl, and HNO3 are added to the fine product (black mass) obtained in the classification process or the magnetic material (black mass magnetic material) obtained in the magnetic separation process, and metal elements such as cobalt, nickel, manganese, and lithium are dissolved in the acidic solution, while copper and carbon are removed as insoluble residues.

[0056] The specific contents of the acid leaching process are not particularly limited as long as cobalt, nickel, and manganese can be leached. For example, the fine product or magnetized material after the addition of acid is heated for a time and temperature described in the Examples section below, and while maintaining the pH value described in the Examples section below, the metal elements in the fine product or magnetized material are thermally decomposed and dissolved in the acid solution. When the change in pH value becomes equal to or less than the value described in the Examples section below, the acid solution is allowed to cool, and the acid solution is filtered to remove the insoluble residue in the acid solution, and the filtrate (acid leaching solution) is recovered. As the acid, H2SO4, HCl, HNO3, etc. can be used, but from the viewpoint of removing copper in this process, it is preferable to use H2SO4.

[0057] As a method for filtration, various methods can be used, such as a membrane filter, filter paper, centrifugation, etc. It is also preferable to use cross-flow filtration.

[0058] (3-6. Iron removal process) This is a process in which an oxidizing agent is added to the recovered filtrate (acid leachate) to adjust the redox potential of the filtrate, and then an alkaline solution is added to generate a precipitate of iron hydroxide and remove the iron.

[0059] The oxidizing agent to be added to the filtrate (acid leachate) may be any known oxidizing agent. Examples include oxygen, ozone, metal oxides, oxygen acids or their salts (e.g., potassium permanganate), and halogens. However, from the viewpoints of ease of use and cost, an aqueous hydrogen peroxide solution is preferred. The redox potential of the filtrate is preferably set at an upper limit of 750 mV (Ag / AgCl; the same applies to redox potentials in this specification, so the description will be omitted hereafter), 700 mV, or 650 mV, and at a lower limit of 500 mV, 550 mV, or 600 mV. Next, the alkaline solution to be added may be a known one. For example, it may be an aqueous solution of an alkali metal hydroxide (aqueous solution of sodium hydroxide and / or aqueous solution of potassium hydroxide). In this specification, an aqueous solution of sodium hydroxide is exemplified. The concentration of the alkaline solution may be 0.5 to 10 mol / L. Then, the pH value of the filtrate is adjusted to 3 to 5.5 to generate a precipitate of iron hydroxide, and the iron hydroxide is aged by maintaining the liquid at a temperature described in the Examples section below for a predetermined time. Thereafter, the filtrate and the iron hydroxide precipitate are filtered, and the filtrate (liquid after iron removal) is collected.

[0060] As a method of filtration, various methods can be used, such as a membrane filter, filter paper, etc. It is also preferable to use cross-flow filtration.

[0061] (3-7. Ion exchange process) In this process, the recovered filtrate (liquid after iron removal) is brought into contact with a specific chelating resin for ion exchange, thereby selectively adsorbing and removing aluminum ions and copper ions, thereby obtaining a filtrate (liquid after ion exchange).

[0062] There are a wide variety of chelating resins with ion exchange capacity. As a result of research, the present inventors have come to the conclusion that, for example, an aminomethyl phosphate-based chelating resin based on a styrene-divinylbenzene copolymer and having aminomethyl phosphate groups is suitable for selectively adsorbing and removing aluminum ions and copper ions from the filtrate (liquid after iron removal). A preferred example of a commercially available product is "IRC747UPS manufactured by DuPont Organo." The aminomethyl phosphate chelating resin is available in Na type and H type, but when using the Na type, the pH value of the filtrate increases after ion exchange, and there is a concern that metal hydroxides may be unintentionally precipitated. Therefore, when using the Na type, it is preferable to adjust the pH value of the filtrate to 3 or less in advance.

[0063] An example of the content of each metal element in the post-ion exchange liquid (or the regenerated positive electrode material precursor described below) is as follows. For aluminum, the upper limit may be 100 mg / L, 50 mg / L, or 10 mg / L. For copper, the upper limit may be 1 mg / L, 0.1 mg / L, or 0.02 mg / L. For iron, the upper limit may be 1 mg / L, 0.5 mg / L, or 0.2 mg / L.

[0064] (3-8. Alkaline treatment process) This is the process where the obtained filtrate (liquid after ion exchange) is mixed with an alkaline solution to adjust the pH value to 9 to 14, and the metal elements in the filtrate, such as cobalt, nickel, manganese, and lithium, are formed as hydroxide precipitates. This process, together with the previous acid leaching process, can be called the hydrometallurgical process.

[0065] For example, 0.5 to 10 mol / L of NaOH aqueous solution is added as an alkaline solution to the collected filtrate, and the pH value of the filtrate is adjusted to 11 to 12 to generate hydroxide precipitate. After the addition of the alkali is completed, the filtrate is filtered and the hydroxide precipitate is collected.

[0066] (3-9. Cleaning process) This is the step of washing the recovered hydroxide precipitate to obtain a regenerated cathode material precursor. For example, the recovered hydroxide precipitate is heated at 20°C to 200°C for 0.1 to 48 hours, and dried under ignition to obtain a dried product. The dried product is pulverized to obtain a pulverized product. The same amount to 10 times the amount (by weight) of water is added to the pulverized product to obtain a slurry. The obtained slurry is filtered to recover the hydroxide precipitate. As a method of filtration, various methods can be used, such as a membrane filter, filter paper, etc. It is also preferable to use cross-flow filtration.

[0067] The recovered hydroxide precipitate is heated at 20° C. to 200° C. for 0.1 hour to 48 hours and dried, to obtain the regenerated positive electrode material precursor according to the present invention. The obtained recycled cathode material precursor is a solid. In the subsequent steps, the recycled cathode material precursor may be handled as a solid or may be made into a slurry. Even if it is made into a slurry, the recycled cathode material precursor contained in the slurry is still a solid. The salt remaining in the hydroxide precipitate may be removed by washing after "(4-3) Calcination step" in "4. Manufacturing method of regenerated positive electrode material" described later.

[0068] It is also preferable to perform a qualitative and quantitative analysis of the metal elements contained in the obtained recycled cathode material precursor according to the present invention. This is because the metal components contained in the recycled cathode material precursor vary depending on the LIB to be treated, and because the metal components contained in the recycled cathode material precursor may vary depending on the process conditions up to this point.

[0069] For example, the metal elements contained in the above-mentioned post-ion-exchange liquid can be subjected to ICP analysis or fluorescent X-ray analysis. When the composition of the metal elements contained in the above-mentioned post-ion-exchange liquid differs from the target metal composition of the regenerated positive electrode material, the above-mentioned post-ion-exchange liquid can be subjected to a compounding process or an adding process.

[0070] Specifically, in response to the difference between the results of the quantitative analysis of the ion-exchanged liquid described above and the target metal composition of the regenerated cathode material precursor, a preparation step can be carried out to adjust the composition of the metal elements contained in the ion-exchanged liquid (for example, a step of appropriately preparing ion-exchanged liquids having different metal compositions derived from different LIBs to obtain a ion-exchanged liquid having the target metal composition, etc.), or an addition step can be carried out to add the missing metal elements to the ion-exchanged liquid. Of course, these steps can also be used in combination.

[0071] [4. Manufacturing method of recycled cathode material] (4-1) Addition of lithium source, etc. The step of adding a lithium source, etc. is a step of adding a predetermined amount of a lithium source, a nickel source, a cobalt source, a manganese source, etc. to the recycled cathode material precursor when there is a difference between the composition of the metal elements that function as the target cathode material in the recycled cathode material and the composition of the metal elements of the obtained recycled cathode material according to the present invention. However, there are few cases where manganese is insufficient in the recycled cathode material precursor.

[0072] Examples of the lithium source include lithium compounds such as lithium carbonate, lithium hydroxide, lithium nitrate, and lithium chloride. Examples of nickel sources include nickel compounds such as nickel carbonate, nickel hydroxide, nickel nitrate, nickel chloride, and nickel sulfate. Examples of the cobalt source include cobalt compounds such as cobalt carbonate, cobalt hydroxide, cobalt nitrate, cobalt chloride, and cobalt sulfate. Examples of manganese sources include manganese compounds such as manganese carbonate, manganese hydroxide, manganese nitrate, manganese chloride, and manganese sulfate.

[0073] The amount of lithium source, etc., added may be an amount necessary to obtain a composition of the recycled positive electrode material that will provide the desired battery characteristics when the resulting recycled positive electrode material is made into a battery. The amount of lithium added is preferably 0.2 to 2.0 times (mol) the total amount (mol) of metal elements that function as the positive electrode material contained in the recycled positive electrode material precursor.

[0074] (4-2) Grinding and mixing process The mixture to which a predetermined amount of lithium source and the like has been added may be pulverized to make it homogenous. The mixture to which a predetermined amount of the lithium source and the like has been added is pulverized to obtain a pulverized mixture. The pulverization can be performed using, for example, a disk mill, a mixer mill, a bead mill, a vibration mill, a ball mill, a planetary ball mill, an attritor, or the like.

[0075] (4-3) Firing process The obtained mixture is fired to obtain the recycled positive electrode material according to the present invention. The firing temperature is preferably 650°C to 900°C. The firing time is preferably 0.1 to 20 hours, more preferably 0.5 to 8 hours. For example, an alumina crucible may be used, and the firing may be performed under holding conditions of 600°C for 1 hour and then 900°C for 4 hours. In the recycled positive electrode material obtained after firing the recycled positive electrode material precursor, iron, copper, and aluminum are oxidized. Specifically, iron, copper, and aluminum, which were mostly hydroxides in the recycled positive electrode material precursor, are oxides in the recycled positive electrode material.

[0076] (4-4) Crushing process The resulting recycled positive electrode material is preferably pulverized using a disk mill or the like to make the recycled positive electrode material into fine particles. The recycled positive electrode material after granulation can be subjected to a washing treatment, and in this case, the firing step can be carried out again after the washing treatment.

[0077] The obtained recycled positive electrode material of the present invention contains lithium, nickel, cobalt, and manganese, 0.01% by mass or more and 1.5% by mass or less of aluminum, and less than 1% by mass of at least one of copper and iron, and can achieve a specific capacity at the same level as LIBs using conventional positive electrode materials, as well as cycle characteristics that are almost comparable to those of LIBs using conventional positive electrode materials.

[0078] [5. How to use recycled cathode materials]

[0079] (5-1) Regenerated positive electrode The recycled positive electrode according to the present invention contains the recycled positive electrode material according to the present invention as a positive electrode active material, and further contains a conductive agent, a binder resin and the like as other components as necessary.

[0080] (5-2) Lithium-ion secondary battery using the recycled positive electrode material according to the present invention The LIB of the present invention is a LIB comprising a positive electrode, a negative electrode, and a separator, where the positive electrode contains the recycled positive electrode material of the present invention. The LIB according to the present invention can be manufactured by a known LIB manufacturing method using the recycled positive electrode material according to the present invention.

[0081] [6. Effects of the present invention] As described above, according to the present invention, the LIB to be treated is subjected to heat treatment, crushing treatment, and classification treatment, which are low-cost treatments that easily reduce the environmental load, to recover a fine product (black mass).The fine product (black mass) is then subjected to magnetic separation treatment, acid leaching treatment, iron removal treatment, ion exchange treatment, alkali treatment, and washing treatment, which are also low-cost treatments that easily reduce the environmental load, making it possible to produce a high-quality recycled positive electrode material precursor with low iron, copper, and aluminum contents. The above effect means that a variety of LIBs can be processed together. In other words, by subjecting a variety of LIBs to the heat treatment process together and then carrying out the above processes, it is possible to produce recycled cathode material precursors and recycled cathode materials. Moreover, this production process can achieve low environmental impact and low recycling costs, while ensuring high safety. With the rapid spread of LIBs in recent years, their recycling has become an issue, and the present invention is considered to have great merits. EXAMPLES

[0082] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples. In addition, in Examples 1 and 2, two types of recycled positive electrode materials were produced by the manufacturing method according to the present invention: a "recycled positive electrode material (without composition adjustment)" in which the recycled positive electrode material precursor was fired without adjusting its composition, and a "recycled positive electrode material (with composition adjustment)" in which the recycled positive electrode material precursor was fired after adjusting its composition. In addition, in Comparative Examples 1 to 3, three types of comparative materials were prepared: a "recycled positive electrode material (conventional type)" produced by a conventional manufacturing method, a "commercially available positive electrode material" prepared from a commercially available positive electrode material (however, the material was re-heated in air at 900°C for 4 hours), and a "trace product of a commercially available positive electrode material" produced by the manufacturing method according to the present invention from a solution in which a commercially available positive electrode material was dissolved in acid (sulfuric acid).

[0083] (Example 1) Recycled cathode material (no composition adjustment) <Heat treatment process> The heat-treated product was obtained by heat-treating the LIB battery pack (approximately 75 kg) to a heat treatment temperature of 800°C (heated up over 1 hour and then held for 2 hours). A batch-type burner furnace manufactured by Ecosystem Akita Co., Ltd. was used as the heat treatment device. During the heat treatment, the inside of the furnace was filled with air at the start of the heat treatment, but the air supply was cut off during the heat treatment.

[0084] <Crushing process> Next, the heat-treated material (LIBs that had been heat-treated) obtained in the heat treatment process was crushed using a hammer crusher (Makino-type swing hammer crusher HC-20-3.7, manufactured by Makino Sangyo Co., Ltd.) as a crushing device under conditions of 50 Hz (hammer peripheral speed 38 m / sec) and a screen at the outlet with a grate-type opening hole of 30 mm x 200 mm, to obtain crushed LIBs.

[0085] <Classification and selection process> Next, the crushed LIB material was sieved using a sieve (diameter 200 mm, manufactured by Tokyo Screen Co., Ltd.) with a mesh size of 1.2 mm, and separated into over-sieve material (coarse product) and under-sieve material (fine product). Then, the fine product (black mass) according to Example 1 was obtained as the under-sieve fine product (black mass). The composition table of the fine product (black mass) is shown in Table 1. Hereinafter, the composition table is a table obtained by ICP analysis. The ICP analysis was performed using an iCAP6300Duo manufactured by Thermo Fisher Scientific (the same applies hereinafter for ICP analysis).

[0086] <Magnetic selection process> The fine product (black mass) of Example 1 was subjected to wet magnetic separation using a drum-type magnetic separator at a magnetic force of 1500 G, a drum rotation speed of 45 rpm, a solid-liquid ratio of 10%, and a slurry supply rate of 100 ml / min to recover the magnetized material (black mass magnetized material) of Example 1. The composition of the magnetized material (black mass magnetized material) is shown in Table 1. Comparing the composition of the fine product (black mass) and the magnetized material (black mass magnetized material) in Table 1, the contents (mass%) of nickel, cobalt, and manganese were increased in the magnetized material compared to the fine product.

[0087] [Table 1]

[0088] <Acid leaching process> 250 g of the recovered magnetized material (black mass magnetized material) according to Example 1 was placed in a 5000 mL upright beaker, 750 mL of ion-exchanged water was added, and the mixture was stirred using a heater-equipped magnetic stirrer while adjusting the liquid temperature to 45°C. A 50% by weight sulfuric acid solution was added thereto so as to maintain the pH at 1, and acid leaching was performed. The end point was determined when the change in pH value per hour was less than 0.02. After the acid leaching solution was allowed to cool, insoluble residues in the acid leaching solution were removed using No. 5C filter paper, and the filtrate (acid leaching solution) was collected. The composition of the filtrate (acid leaching solution) is shown in Table 2.

[0089] <Iron removal process> An oxidizing agent (hydrogen peroxide aqueous solution) was added to the filtrate (acid leachate) to adjust the redox potential to 634 mV (Ag / AgCl). An alkaline solution was then added to the filtrate with the adjusted redox potential to adjust the pH value to 4.42, producing a precipitate of iron hydroxide. The filtrate was then kept at a liquid temperature of 40°C for 12 hours to mature the iron hydroxide, after which the filtrate (acid leachate) and the iron hydroxide precipitate were separated by filtration, and the filtrate (liquid after iron removal) was recovered. The composition of the filtrate (liquid after iron removal) is shown in Table 2.

[0090] <Ion exchange process> A PVC column with an inner diameter of 40 mm was packed with 150 mL of AmberSep IRC747 UPS manufactured by DuPont Organo as a chelating resin to prepare an ion exchange column. The filtrate (liquid after iron removal), which had been adjusted to pH 2.90 by adding 50% by weight of sulfuric acid solution, was passed through the column at a flow rate of 25.0 mL / min (SV=10) to remove aluminum ions, and a filtrate (liquid after ion exchange) was obtained. The composition of the filtrate (liquid after ion exchange) is shown in Table 2.

[0091] [Table 2]

[0092] <Alkaline treatment process> The obtained filtrate (liquid after ion exchange) was mixed with an aqueous NaOH solution having a concentration of about 7.5 mass % to adjust the pH value to 11.3, and the hydroxide was precipitated. The hydroxide was then collected using No. 5C filter paper.

[0093] <Cleaning process> A sufficient amount of ion-exchanged water was poured into the hydroxide collected on the filter paper to wash away water-soluble salts, and then the hydroxide was dried in a vacuum thermostatic chamber at 85°C to obtain a regenerated cathode material precursor sample.

[0094] <Crushing process> The resulting recycled positive electrode material precursor sample was pulverized using a disk mill to obtain a pulverized product.

[0095] <Lithium doping process> Lithium was added as lithium carbonate in an amount equivalent to 1.0 times the molar amount of the metal elements contained in the pulverized precursor that function as a positive electrode material, and mixed in a mortar. <Firing process> The mixture was placed in an alumina crucible and fired in an air atmosphere at 600°C for 1 hour and then at 900°C for 4 hours to obtain a recycled positive electrode material sample.

[0096] <Crushing process> The resulting recycled positive electrode material sample was pulverized using a mortar. The obtained regenerated cathode material sample was subjected to acid decomposition with a mixed acid of HCl and HNO3, and then the composition was analyzed using ICP-AES (SPECTRO GREEN, Hitachi High-Tech Science Corporation). Table 3 shows the composition of the recycled positive electrode material sample, with the constituent elements listed in mass %. The composition, expressed in moles per 100 g, is shown in Table 4. The mole ratios of the specified elements calculated from the number of moles per 100 g are shown in Table 5. Note that MCN is the total number of moles of Mn, Co, and Ni, and MCNCuFeAl is the total number of moles of Mn, Co, and Ni plus the number of moles of Cu, Fe, and Al. The recycled positive electrode material (with crude composition adjustment), recycled positive electrode material (conventional type), commercially available positive electrode material, and trace products of commercially available positive electrode material described below are also listed in the above tables.

[0097] (Example 2) Recycled cathode material (with composition adjustment) <Addition process> In the above-mentioned Example 1, a composition analysis was performed on the filtrate (liquid after ion exchange) obtained in the ion exchange step. As a result, compared with the manganese, cobalt, and nickel contained in the commercially available positive electrode material used in Comparative Example 2, sulfuric acid solutions of cobalt hydroxide and nickel hydroxide were added to adjust the insufficient cobalt and nickel, and the composition was adjusted. <Alkaline treatment process> The obtained composition-adjusted liquid was mixed with an aqueous NaOH solution having a concentration of about 7.5 mass % to adjust the pH value to 11.3, and the hydroxide was precipitated. The hydroxide was then collected using No. 5C filter paper.

[0098] <Cleaning process> A sufficient amount of ion-exchanged water was poured into the hydroxide collected on the filter paper to wash away water-soluble salts, and then the hydroxide was dried in a vacuum thermostatic chamber at 85°C to obtain a regenerated cathode material precursor sample.

[0099] <Crushing process> The resulting recycled positive electrode material precursor sample was pulverized using a disk mill to obtain a pulverized product. <Lithium doping process> Lithium was added as lithium carbonate in an amount equivalent to 1.1 times the molar amount of the metal elements contained in the pulverized precursor that function as a positive electrode material, and the mixture was mixed in a mortar. The rest of the process was the same as in Example 1 to obtain a recycled positive electrode material of this example.

[0100] (Comparative Example 1) Recycled cathode material (conventional type) Except for not carrying out the iron removal step and the ion exchange step, the same steps as those for the recycled cathode material of Example 1 were carried out to obtain a recycled cathode material (conventional type) of this example. The obtained sample was subjected to composition analysis in the same manner as in Example 1.

[0101] (Comparative Example 2) Commercially available cathode material The commercially available cobalt-nickel-manganese cathode material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, PLB-H1, manufactured by Gelon LIB Group Ltd.) were prepared. The cobalt-nickel-manganese based positive electrode material was calcined again in air at 900° C. for 4 hours to obtain a commercially available positive electrode material. The composition of the obtained sample was analyzed in the same manner as in Example 1.

[0102] (Comparative Example 3) Trace of commercially available positive electrode material A commercially available normal cobalt-nickel-manganese positive electrode material was dissolved in acid, and the obtained solution was subjected to the same processes as in the examples, namely, the alkali treatment process, the washing process, the crushing process, the baking process, and the crushing process, to obtain a trace of the commercially available positive electrode material. The obtained sample was subjected to the composition analysis in the same manner as in Example 1.

[0103] [Table 3]

[0104] [Table 4]

[0105] [Table 5]

[0106] 2. Manufacturing of lithium-ion secondary batteries <Production of positive electrodes> As the positive electrode active material, the positive electrode materials obtained in the above-mentioned Examples 1 and 2 and Comparative Examples 1 to 3 were prepared. Acetylene black (Denka Black, manufactured by Denka Co., Ltd.) was prepared as a conductive assistant, polyvinylidene fluoride (KF Polymer F #9130, manufactured by Kureha Co., Ltd.) was prepared as a binder, and N-methylpyrrolidone was prepared as a solvent.

[0107] Then, each of the positive electrode materials was mixed with acetylene black and polyvinylidene fluoride in a ratio of 80:10:10 (mass%) to prepare a mixture. N-methylpyrrolidone was added to the mixture to obtain a slurry. The amount of N-methylpyrrolidone added to the mixture was the mixture:N-methylpyrrolidone=1:1.25 in mass ratio. The obtained slurry was stirred with a stirrer for 10 minutes, and then the slurry was applied to an aluminum foil (t20μm) as a current collector of the positive electrode material using a Baker-type applicator. Then, the aluminum foil was dried together with the positive electrode material in a dryer at 100°C. The dried aluminum foil and the positive electrode material applied thereon were pressed with 4t, and then punched to a diameter of φ15mm to form a positive electrode.

[0108] <Production of negative electrodes> Graphite (CGB-10, manufactured by Nippon Graphite Industries Co., Ltd.) was prepared as the negative electrode active material, acetylene black (Denka Black, manufactured by Denka Co., Ltd.) as the conductive additive, carboxymethylcellulose (Cellogen 7A, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and styrene-butadiene rubber (TRD2001, manufactured by JSR Corporation) as the binder, and pure water as the solvent. Then, graphite: acetylene black: carboxymethyl cellulose: styrene-butadiene rubber were mixed in a ratio of 90: 5: 2.5: 2.5 (mass%). Distilled water was added to the mixture to obtain a slurry. The amount of distilled water added to the mixture was such that the mass ratio of the mixture: distilled water was 1: 1.6. The obtained slurry was stirred for 10 minutes with a stirrer, and then the slurry was applied to copper foil (thickness 20 μm) as a current collector for the graphite negative electrode material using a Baker-type applicator. The slurry was then dried together with the copper foil in a dryer at 100°C. The dried copper foil and the negative electrode material applied thereon were pressed with a 4t pressure, and then punched out to a diameter of φ15 mm to form a negative electrode.

[0109] <Assembling lithium-ion secondary batteries> In a glove box filled with pure argon gas, a CR2032 coin cell was used and the following layers were stacked in this order, as shown in Figure 2: positive electrode collector (stainless steel) 1, positive electrode (aluminum foil collector coated with positive electrode material) 2, separator 3, gasket 4, negative electrode (copper foil collector coated with negative electrode material) 5, spacer 6, washer 7, and negative electrode collector (stainless steel) 8. Then, full cells of lithium ion secondary batteries using each of the positive electrode materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3 were assembled by crimping a stainless steel positive electrode current collector and a negative electrode current collector.

[0110] The separator was a porous polypropylene (#2500, Celgard LLC) with a diameter of φ19 mm, and the electrolyte was a solute of LiPF6 with a concentration of 1 mo1 / L and a solvent of ethylene carbonate + diethyl carbonate (volume ratio 1:1). In the case of full cells, the assumed specific capacity of the normal positive electrode material and the recycled positive electrode material was 140mAh / g or 150mAh / g, depending on the range of cell voltage change during charging and discharging. The assumed specific capacity of the graphite negative electrode material was 340mAh / g. The ratio of the negative electrode capacity to the positive electrode capacity (NP ratio) was 1.2. The assumed specific capacity of the positive electrode material used in the full cells will be specified in each case.

[0111] Next, half cells of lithium ion secondary batteries were assembled using each of the positive electrode materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3 in the same manner as in the full cells of the lithium ion secondary batteries described above. The configuration of the half cells is the same as that of the full cells, except that the graphite negative electrode was replaced with a lithium foil having a diameter of 15 mm and a thickness of 0.2 mm. In the case of the half cells, the assumed specific capacity of the normal positive electrode material and the recycled positive electrode material was set to 140 mAh / g or 150 mAh / g depending on the range of change in the potential of the positive electrode. The assumed specific capacity of the positive electrode material used in the half cells will also be specified in each case.

[0112] 3.Charge and discharge test of lithium-ion secondary battery Charge / discharge tests were carried out by cycle tests on the half cells and full cells of the manufactured lithium ion secondary batteries as described below, and the charge / discharge specific capacity and coulombic efficiency (charge / discharge efficiency, hereinafter simply referred to as efficiency) of each of the positive electrode materials obtained in Examples 1 and 2 and Comparative Examples 1 to 3 were measured. In the half cells and full cells, the capacity measured during charging and discharging the cell was divided by the mass of the regenerated positive electrode material in the cell to evaluate the cell performance in terms of the positive electrode standard specific capacity.

[0113] <Charge / discharge test on positive electrode half cell> (Rate test of positive half cell) The positive electrode was charged and discharged, i.e., lithium ions were desorbed and inserted, under the conditions described below, and the specific capacity and coulombic efficiency were measured. (1) Recycled cathode material (no composition adjustment), (2) Recycled cathode material (with composition adjustment), (3) Recycled cathode material (conventional type), (4) Commercially available cathode material, (5) Traceable version of commercially available cathode material: Estimated specific capacity of cathode material: 140mAh / g (based on the amount of cathode material) Test temperature: 25℃ Positive electrode potential range: 3.0V~4.2VvsLi / Li + Current density: 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, 0.1C (1C = 140mA / g (based on the amount of positive electrode material)) Number of cycles: 5 at each current density

[0114] The measurement items are listed below. (I) Specific capacity at 0.1C, first cycle, charging (lithium ion desorption). This value indicates the amount of lithium ions released during the process in which lithium ions are initially extracted from the positive electrode material. (II) Specific capacity at 0.1C, first cycle, discharge (lithium ion insertion). This value indicates the amount of lithium ions inserted during the process in which lithium ions are first extracted from the positive electrode material and then returned to the positive electrode material. (III) 0.1C, 1st cycle, coulombic efficiency during charging and discharging. This value indicates the extent to which the desorbed lithium ions return to the positive electrode material during the desorption and insertion of lithium ions in the initial positive electrode material. (IV) Specific capacity at 0.1C, third cycle, discharge (lithium ion insertion). This value indicates the reversible amount of lithium ions in the positive electrode material when the current density is at its lowest and the repeated desorption and insertion of lithium ions in the positive electrode material occurs slowly and stabilizes to a certain degree. (V) Specific capacity at 10C, third cycle, discharge (lithium ion insertion). This value indicates the reversible handling capacity of lithium ions in the positive electrode material at the highest current density, and indicates the degree to which it can handle high-speed charging and discharging. (VI) Specific capacity during the third cycle discharge (lithium ion insertion) at 0.1C in the second stage after testing at 10C. This value indicates the reversible handling capacity of lithium ions in the positive electrode material when the repeated desorption and insertion of lithium ions in the positive electrode material is sufficiently slow and stabilized after 35 cycles of charging and discharging at current densities varying from 0.1C to 10C. The rate test results of the positive half-cell are shown in Table 6.

[0115] From the results in Table 6, it was found that the conventional recycled cathode material with a high aluminum content (Comparative Example 1) had low specific capacity and Coulombic efficiency. In contrast, it was found that the recycled cathode material with a reduced aluminum content (Examples 1 and 2) had specific capacity and Coulombic efficiency values ​​close to those of the commercially available cathode material traced (Comparative Example 3). Furthermore, it was found that the recycled cathode material (Example 2) in which the composition of lithium, nickel, and cobalt was adjusted had specific capacity and Coulombic efficiency values ​​almost comparable to those of the commercially available cathode material (Comparative Example 2) and the commercially available cathode material traced (Comparative Example 3), and in some cases even higher values ​​were obtained.

[0116] [Table 6]

[0117] <Full cell charge / discharge test> (A) (Full cell rate test) Charge and discharge were carried out at a constant current density under the following conditions. (1) Recycled cathode material (no composition adjustment), (2) Recycled cathode material (with composition adjustment), (3) Recycled cathode material (conventional type), (4) Commercially available cathode material, (5) Traceable version of commercially available cathode material: Estimated specific capacity of cathode material: 140mAh / g (based on the amount of cathode material) Test temperature: 25℃ Cell voltage range: 2.5V~4.2V (initial charge: 0V~4.2V) Current density: 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, 0.1C (1C = 140mA / g (based on the amount of positive electrode material)) Number of cycles: 5 at each current density

[0118] The measurement items are listed below. (I) Specific capacity at 0.1C, 1st cycle, charging This value indicates the amount of lithium ions released from the positive electrode material during the initial charging process of a full cell. (II) Specific capacity at 0.1C, 1st cycle, discharge This value indicates the amount of lithium ions inserted into the positive electrode material when the full cell is initially charged and then discharged. (III) 0.1C, 1st cycle, coulombic efficiency during charging and discharging This value indicates how much discharging is required for the lithium ions released during charging to return to the positive electrode material during the initial full cell charge / discharge process. (IV) 0.1C, 3rd cycle, specific capacity upon discharge This value indicates the reversible amount of lithium ions that can be handled in the positive electrode material when the current density is at its lowest and repeated charging and discharging of a full cell is slow and stabilized to a certain extent. (V) 10C, 3rd cycle, specific capacity during discharge This value indicates the reversible handling amount of lithium ions in the positive electrode material during charging and discharging at the highest current density, and indicates the degree of compatibility with high-speed charging and discharging. (VI) Specific capacity during discharge at 0.1C in the second stage after charge / discharge test at 10C This value indicates the reversible handling capacity of lithium ions in the positive electrode material when repeated charging and discharging in a full cell is slow and stable after 35 cycles of charging and discharging with current densities ranging from 0.1C to 10C. The full cell rate test results are listed in Table 7.

[0119] From the results in Table 7, it was found that the conventional recycled cathode material with a high aluminum content (Comparative Example 1) had low specific capacity and Coulombic efficiency. In contrast, it was found that the recycled cathode material with a reduced aluminum content (Examples 1 and 2) showed values ​​close to those of the commercially available cathode material (Comparative Example 2) and a trace of the commercially available cathode material (Comparative Example 3) in terms of specific capacity and Coulombic efficiency. In particular, it was found that the recycled cathode material (Example 2) in which the composition of nickel and cobalt was adjusted had performance comparable to that of the cathode material using virgin material in Comparative Examples 2 and 3 in terms of specific capacity and Coulombic efficiency.

[0120] [Table 7]

[0121] (B) (Full cell cycle test) After the rate test of the full cell, a predetermined number of charge / discharge cycles were performed at a constant current density under the following conditions. Test temperature: 25℃ Cell voltage range: 2.5V~4.2V Current density: 2C (280mA / g (based on the amount of positive electrode material)) Number of cycles: 500

[0122] The measurement items are listed below. (I) Specific capacity during discharge in the first cycle This value indicates the amount of lithium ions released from the positive electrode material when a full cell is discharged for the first time during a realistic charge / discharge cycle at a current density of 2C, which is the current density required to complete charging or discharging a full cell in 30 minutes. (II) Specific capacity at discharge, 200th cycle This value indicates the amount of lithium ions released from the positive electrode material after a full cell has been charged and discharged 200 times at a current density of 2 C. For lithium-ion secondary batteries, this assumes performance in the early to middle life stages when the product is stable. (III) Retention rate of discharge specific capacity at the 200th cycle and the 1st cycle This value indicates the cycle durability of the full cell after 200 charge / discharge cycles, i.e., from the early to mid-life stages. (IV) Specific capacity at discharge, 500th cycle This value indicates the amount of lithium ions released from the positive electrode material after a full cell is charged and discharged 500 times at a current density of 2 C. It assumes the product's performance at the final stage of its life. (V) Discharge specific capacity retention rate at 500th cycle and 1st cycle This value indicates the cycle durability of a full cell after 500 charge / discharge cycles, i.e., until the end of its life stage. The full cell cycle test results are listed in Table 8.

[0123] From the results of Table 8, the conventional recycled positive electrode material with a high aluminum content (Comparative Example 1) had a specific capacity retention rate comparable to other positive electrode materials, but the specific capacity itself was small. In contrast, the recycled positive electrode materials (Examples 1 and 2) in which the aluminum content was reduced had a higher specific capacity and a higher specific capacity retention rate than the conventional recycled positive electrode materials. In particular, the recycled positive electrode material (Example 2) in which the composition of nickel and cobalt was adjusted showed a specific capacity and its retention rate equivalent to those of the commercially available positive electrode material (Comparative Example 2) and a trace product of the commercially available positive electrode material (Comparative Example 3), and was found to have cycle durability comparable to that of a positive electrode material using virgin material.

[0124] [Table 8]

[0125] <Charge / discharge test on positive half-cell at high potential> (Rate test of positive half-cell at high potential) When the positive electrode material undergoes desorption / insertion of lithium ions at high potential, the specific capacity of the positive electrode material increases, and the amount of charge stored in the full cell (energy density) increases. On the other hand, when the positive electrode material is exposed to a high potential, i.e., a highly oxidizing atmosphere, it becomes difficult for the positive electrode material to operate stably. This test evaluates the specific capacity and operational stability of the positive electrode material during charge / discharge at high potential. The positive electrode was charged and discharged, i.e., lithium ions were desorbed and inserted, under the conditions described below, and the specific capacity and coulombic efficiency were measured. (1) Recycled cathode material (no composition adjustment), (2) Recycled cathode material (with composition adjustment), (3) Recycled cathode material (conventional type), (4) Commercially available cathode material, (5) Traceable version of commercially available cathode material: Estimated specific capacity of cathode material: 150mAh / g (based on the amount of cathode material) Test temperature: 25℃ Positive electrode potential range: 3.0V~4.5VvsLi / Li + Current density: 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, 0.1C (1C=150mA / g (based on the amount of positive electrode material)) Number of cycles: 5 at each current density

[0126] The measurement items are listed below. (I) Specific capacity at 0.1C, 1st cycle, charging (lithium ion desorption) (II) Specific capacity at 0.1C, 1st cycle, discharge (lithium ion insertion) (III) 0.1C, 1st cycle, coulombic efficiency during charging and discharging (IV) 0.1C, 3rd cycle, specific capacity at discharge (lithium ion insertion) (V) Specific capacity at 10C, 3rd cycle, discharge (lithium ion insertion) (VI) Specific capacity during the third discharge cycle (lithium ion insertion) at 0.1C in the second stage after testing at 10C The rate test results of the positive half-cells at high potential are listed in Table 9.

[0127] From the results in Table 9, the conventional recycled cathode material with a high aluminum content (Comparative Example 1) had a VvsLi / Li of 4.5V. + It was found that even when lithium ions were desorbed until the high potential of the regenerated cathode material was reached, both the specific capacity and the Coulombic efficiency were low. The specific capacity and the Coulombic efficiency of the regenerated cathode material (Examples 1 and 2) in which the aluminum content was reduced were close to those of the commercially available cathode material (Comparative Example 2) and the trace product of the commercially available cathode material (Comparative Example 3). In particular, the regenerated cathode material (Example 2) in which the composition of nickel and cobalt was adjusted showed performance comparable to that of the cathode material using the virgin material in Comparative Examples 2 and 3. In other words, it was found that by reducing the aluminum content, the regenerated cathode material can achieve high specific capacity and stable desorption and insertion of lithium ions even at high potentials.

[0128] [Table 9]

[0129] <Full-cell charge / discharge test at high cell voltage> (A) (Full cell rate test at high cell voltage) When a full cell is charged and discharged at high voltage, the amount of stored electricity (energy density) of the full cell increases. On the other hand, since more lithium ions are released from the positive electrode material, it is exposed to a high potential, i.e., a highly oxidizing atmosphere, making stable operation of the full cell difficult. Therefore, we evaluate the specific capacity and operational stability of the full cell when charging and discharging at high voltage. Charge and discharge were carried out at a constant current density under the following conditions. (1) Recycled cathode material (no composition adjustment), (2) Recycled cathode material (with composition adjustment), (3) Recycled cathode material (conventional type), (4) Commercially available cathode material, (5) Traceable version of commercially available cathode material: Estimated specific capacity of cathode material: 150mAh / g (based on the amount of cathode material) Test temperature: 25℃ Cell voltage range: 2.5V~4.4V (initial charge: 0V~4.4V) Current density: 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, 0.1C (1C=150mA / g (based on the amount of positive electrode material)) Number of cycles: 5 at each current density

[0130] The measurement items are listed below. (I) Specific capacity at 0.1C, 1st cycle, charging (II) Specific capacity at 0.1C, 1st cycle, discharge (III) 0.1C, 1st cycle, coulombic efficiency during charging and discharging (IV) 0.1C, 3rd cycle, specific capacity upon discharge (V) 10C, 3rd cycle, specific capacity during discharge (VI) Specific capacity during discharge at 0.1C in the second stage after charge / discharge test at 10C The full cell rate test results at high cell voltages are listed in Table 10.

[0131] From the results in Table 10, the conventional recycled cathode material with a high aluminum content (Comparative Example 1) had low specific capacity and coulombic efficiency even at high cell voltages. It was confirmed that the recycled cathode materials with reduced aluminum content (Examples 1 and 2) had specific capacity and initial coulombic efficiency close to those of commercially available cathode materials and their traceable products, even when charged and discharged at high cell voltages.

[0132] [Table 10]

[0133] (B) (Full cell cycle test at high cell voltage) After a rate test at a full cell high voltage (2.5 V to 4.4 V), a predetermined number of charge / discharge cycles were performed at a constant current density and high cell voltage under the following conditions. Test temperature: 25℃ Cell voltage range: 2.5V~4.4V Current density: 2C (300mA / g (based on the amount of positive electrode material)) Number of cycles: 500

[0134] The measurement items are listed below. (I) Specific capacity during discharge in the first cycle (II) Specific capacity at discharge, 200th cycle (III) Retention rate of discharge specific capacity at the 200th cycle and the 1st cycle (IV) Specific capacity at discharge, 500th cycle (V) Discharge specific capacity retention rate at 500th cycle and 1st cycle This value is after 500 charge / discharge cycles, i.e., at the end of its lifespan. The full cell high voltage cycling test results are listed in Table 11.

[0135] From the results of Table 11, the conventional recycled cathode material with a high aluminum content (Comparative Example 1) had a lower specific capacity and its retention rate than other cathode materials. The recycled cathode materials with reduced aluminum content (Examples 1 and 2) had a higher specific capacity and a higher specific capacity retention rate than the conventional recycled cathode materials. In particular, the recycled cathode material with nickel and cobalt composition adjustment (Example 2) had a low initial specific capacity, but the specific capacity gradually increased by repeating charge and discharge, and extremely high cycle stability was observed. The commercially available cathode material (Comparative Example 2) also had a tendency to increase its specific capacity up to 200 cycles, and in the case of cycle tests at high voltages of 2.5V to 4.4V, a different appearance was observed from the tests at normal voltages of 2.5V to 4.2V. The specific capacity of the recycled cathode material with reduced aluminum content after 500 cycles was lower than that of the commercially available cathode material, but was higher than that of the trace product of the commercially available cathode material (Comparative Example 3), and the specific capacity retention rate after 500 cycles was not low. In other words, even when charged and discharged at high voltages, the recycled positive electrode material with reduced aluminum content exhibited cycle durability comparable to that of positive electrode materials using virgin materials.

[0136] [Table 11] [Explanation of symbols]

[0137] 1: Positive electrode current collector 2: Positive electrode 3: Separator 4: Gasket 5: Negative electrode 6: Spacer 7: Washer 8:Negative electrode current collector 10: Lithium-ion secondary battery

Claims

1. A method for producing a recycled positive electrode material precursor from a lithium ion secondary battery, which is an object to be treated, comprising the steps of: a heat treatment step of heating the lithium ion secondary battery as the object to be treated to obtain a heat-treated product; A crushing step of crushing the heat-treated product to obtain a crushed product; A classification and selection step of performing classification and selection on the crushed product to obtain a fine product; an acid leaching step of subjecting the fine product to acid leaching to obtain an acid leachate; an iron removing step of adding an oxidizing agent and an alkali to the acid leaching solution to obtain an iron-removed solution; an ion exchange step of contacting the iron-removed liquid with a chelating resin to obtain an ion-exchanged liquid; an alkali treatment step of adding an alkali to the post-ion exchange liquid to generate a precipitate; and a washing step of washing the precipitate with water to obtain a regenerated cathode material precursor.

2. The method for producing a recycled positive electrode material precursor according to claim 1 , further comprising the step of: after the classification step, performing a magnetic separation step of magnetically separating the fine product to obtain a magnetically-attached material.

3. The method for producing a regenerated cathode material precursor according to claim 1 , wherein the acid leaching step is performed using sulfuric acid.

4. The method for producing a regenerated cathode material precursor according to claim 1, wherein the iron removing step is performed by using an aqueous hydrogen peroxide solution as an oxidizing agent and setting the oxidation-reduction potential of the acid leaching solution to 500 to 750 mV (Ag / AgCl).

5. The method for producing a regenerated positive electrode material precursor according to claim 1 , wherein the ion exchange step is performed using an aminomethyl phosphate-based chelating resin as the chelating resin to remove aluminum ions.

6. 2. The method for producing a recycled positive electrode material precursor according to claim 1, further comprising: carrying out an analysis step of quantitatively analyzing metal elements contained in the post-ion-exchange liquid; and carrying out a preparation step of preparing the post-ion-exchange liquid when there is a difference between the result of the quantitative analysis of the metal elements contained in the post-ion-exchange liquid and a target metal composition of the recycled positive electrode material precursor.

7. 2. The method for producing a recycled positive electrode material precursor according to claim 1, further comprising: carrying out an analysis step of quantitatively analyzing metal elements contained in the post-ion-exchange liquid; and, if there is a difference between the result of the quantitative analysis of the metal elements contained in the post-ion-exchange liquid and the target metal composition of the recycled positive electrode material precursor, carrying out an addition step of adding metal elements that are insufficient in the target metal composition of the recycled positive electrode material precursor.

8. 7. The method for producing a recycled positive electrode material precursor according to claim 6, wherein the prepared post-ion exchange solution has an aluminum content of 100 mg / L or less, a copper content of 1 mg / L or less, and an iron content of 1 mg / L or less.

9. 8. The method for producing a recycled positive electrode material precursor according to claim 7, wherein the post-ion-exchange solution to which the metal elements have been added has an aluminum content of 100 mg / L or less, a copper content of 1 mg / L or less, and an iron content of 1 mg / L or less.

10. A method for producing a recycled cathode material, comprising adding a predetermined metal compound to a recycled cathode material precursor produced by the method for producing a recycled cathode material precursor according to any one of claims 1 to 9, and then calcining the mixture to obtain a recycled cathode material.

11. The method for producing a recycled positive electrode material according to claim 10, wherein the metal compound is at least one selected from the group consisting of a lithium compound, a nickel compound, a cobalt compound, and a manganese compound.

12. An assembly process for assembling a lithium ion secondary battery having the recycled positive electrode material according to claim 10; and an activation step of charging and discharging the lithium ion secondary battery assembled in the assembly step.

Citation Information

Patent Citations

  • Transfer mechanism of paper card

    JP1983047742A

  • Recycled cathode material precursor, recycled cathode material, their manufacturing methods, and recycled lithium-ion secondary battery

    JP7176707B1